2009
DOI: 10.1242/jeb.034066
|View full text |Cite
|
Sign up to set email alerts
|

Stress hormones and the fitness consequences associated with the transition to a novel diet in larval amphibians

Abstract: SUMMARY Closely related species often specialize on different types of prey, but little is known about the fitness consequences of making an evolutionary transition to a novel diet. Spadefoot toad larvae provide a unique opportunity to reconstruct these evolutionary events. Although most anuran larvae feed on detritus or plankton, Spea larvae have also evolved the ability to consume large anostracan fairy shrimp. To investigate the changes that may have accompanied the shift to shrimp prey, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…For example, when nutritionally restricted, couch's spadefoot toad (Scaphiopus couchii) tadpoles exhibited higher levels of whole-body corticosterone (Crespi and Denver 2005;Ledon-Rettig et al 2009). Because the hypothalamic-pituitary-interrenal (similar to the hypothalamic-pituitary-adrenal axis in mammals) and immune system function are coupled (Rollins-Smith 2001), it would not be surprising if increased corticosterone mediated either of the immune responses that we measured.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when nutritionally restricted, couch's spadefoot toad (Scaphiopus couchii) tadpoles exhibited higher levels of whole-body corticosterone (Crespi and Denver 2005;Ledon-Rettig et al 2009). Because the hypothalamic-pituitary-interrenal (similar to the hypothalamic-pituitary-adrenal axis in mammals) and immune system function are coupled (Rollins-Smith 2001), it would not be surprising if increased corticosterone mediated either of the immune responses that we measured.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the key role of GCs as metabolic regulators described earlier, there is a large accumulation of empirical support for the idea that the neuroendocrine stress axis is an evolutionarily conserved regulator of transitions in early life-history stages across vertebrates (Denver 2009). Elevation in HPA/I axis activity has been described prior to metamorphosis in amphibians and fish, birth in mammals (reviewed in Crespi & Denver 2005a;Wada 2008), and hatching in most oviparous vertebrates (birds, reptiles and some amphibians) but not in fish (reviewed in Wada 2008;Ledon-Rettig, Pfennig & Crespi 2009). Increases in GCs have also been associated with the transition between freshwater to saltwater life-history stages in anadromous fish (reviewed in Wada 2008).…”
Section: Do Gcs Mediate Age-dependent Life-history Transitions?mentioning
confidence: 99%
“…For example, life-history theory would predict that species with relatively fast tadpole growth and development rates should have higher baseline GC levels to maintain high amounts of circulating energetic resources needed for rapid growth, and relatively earlier HPI axis maturation to allow for earlier onset of metamorphosis. Indeed, in spadefoot toads (Family Scaphiopodidae) Ledon-Rettig, Pfennig & Crespi (2009) found that Scaphiopus couchii, one of the fastest developing species, had higher baseline corticosterone levels compared with the more slowly developing Spea bombifrons. Buchholz & Hayes (2005) found higher thyroid hormone (TH) levels in faster developing spadefoot toads, and because CRF stimulates TH and GCs in tadpoles, corticosterone is likely to be higher in these animals too.…”
Section: Do Gcs Mediate Age-dependent Life-history Transitions?mentioning
confidence: 99%
“…This situation is comparable with data on Spea larvae, in which fast growth and fast development occur in wild populations in semi arid environments of North America. Spea larvae are facultative carnivores that express alternate resource-use phenotypes that are adaptive for either detritus or shrimp (Pfennig et al 1993;Ledón-Rettig et al 2009.…”
Section: Heterocrhony In Ceratophryinesmentioning
confidence: 99%